A method based on SVD for detecting the defect using the magnetostrictive guided wave technique. (March 2016) - Tang, Mingxi; Wu, Xinjun; Cong, Ming; Guo, Kai
Abstract: Magnetostrictive guided wave testing is a useful non-contact nondestructive testing method. However the signal to noise ratio (SNR) of its testing signal is low due to the lift-off. In this paper, a novel index called singular decreasing index (SDI) is proposed to distinguish the defect signal, which is based on a new matrix form improved from the Hankel matrix and the singular value decomposition (SVD). Further, an SDI spectrum is proposed to locate defects. Simulation signals with different SNR are employed to evaluate the performance of this method, and results show that the SDI spectrum can locate the defect at a very low SNR. Experimental results also show the excellent performance of the SDI spectrum in defect location. Hence, it is believed that this method can effectively detect defects at low SNR. Highlights: The Hankel matrix is improved to process the magnetostrictive guided wave signal. An index called SDI is proposed to identify the defect signal based on the SVD. The SDI spectrum is used to locate the defect signal while the SNR is low. Good performances have been proved through simulation and experimental signals.